Monetary commitment and the level of public debt - Stefano Gnocchi; Luisa Lambertini (Bank of Canada, 2016)
We analyze the interaction between committed monetary policy and discretionary fiscal policy in a model with public debt, endogenous government expenditures, distortive taxation and nominal rigidities. Fiscal decisions lack commitment but are Markovperfect. Monetary commitment to an interest rate path leads to a unique level of debt. This level of debt is positive if the central bank adopts closed-loop strategies that raise the real interest rate when inflation is above target owing to fiscal deviations. More aggressive defence of the inflation target implies lower debt and higher welfare. Simple Taylor-type interest rate rules achieve welfare levels similar to those generated by sophisticated closed-loop strategies.
Keywords: E24; E32; E52; 330; Credibility; Fiscal policy; Inflation targets; Monetary policy framework